Synthesis of 2-[4-(10H-Substituted Phenothiazine-3-yl)-6-Pyrimidin-2-Phenylthiol/ol/amine/thiol] Pyrroles - Meghasham Narule; Jyotsna Meshram; B. Santhakumari; A. Shanware (E-Journal of Chemistry)
2-[4-Hydroxy benz-1(propene-1-one)]Pyrrole II on treatment with phenyl thiourea, guanidine carbonate, urea and thiourea in alcoholic KOH yielded compounds III, IV, V, VI which on treatment with different aryl anilines gave compounds VII, VIII, IX, X which under goes cyclisation with sulphur and iodine to give 2-[4-(10H-substituted phenothiazine-3-yl)-6-pyrimidin-2-phenylthiol/-ol/-amine/-thiol] pyrrole XI(a-j), XII(a-j), XIII(a-j) and XIV(a-j) respectively. The structural products were characterized by elemental analysis and spectral data.